Nutritional state and exercise performance in patients with chronic obstructive lung disease. - Schols, A M (1989)
The relation between exercise performance and certain measures of nutritional state was investigated in 83 patients with stable chronic obstructive lung disease (mean age 62 (8) years). All patients had a forced expiratory volume in one second (FEV1) less than 50% predicted, an arterial oxygen tension of more than 7.3 kPa, and no severe locomotor, cardiovascular, neurological, or endocrine disorders. Exercise performance was assessed from a 12 minute walking test; body weight (as a percentage of ideal weight), creatinine height index, and serum concentrations of albumin, transferrin, and prealbumin were assessed as measures of nutritional state. Mean values of the nutritional variables were within the normal range. The mean (SD) 12 minute walking distance was 686 (254) metres. Walking distance was positively associated with serum albumin concentration and creatinine height index but not with body weight, serum prealbumin, or serum transferrin concentrations. When patients were categorised into low, medium and high performance groups on the basis of their walking distance, a very low creatinine height index (mean (SD) 59% (19%] was found in the low performance group. Albumin explained part of the variance in walking distance independently of pulmonary function in a stepwise regression analysis. The findings suggest that in patients with chronic airflow obstruction skeletal muscle mass and serum albumin concentration are positively associated with exercise performance as measured with a 12 minute walk.